Dietary supplementation with calcium peroxide improves methane mitigation potential of finishing beef cattle - E. Roskam; D.A. Kenny; A.K. Kelly; V. O’Flaherty; S.M. Waters (Animal)
Calcium peroxide (CaO2) offers potential as an anti-methanogenic dietary feed material. The compound has been previously assessed in vitro, with methane (CH4) reductions of > 50% observed. The objective of this study was to assess dietary supplementation of CaO2 at different inclusion levels and physical formats in a finishing beef system on the effects of animal performance, gaseous emissions, rumen fermentation parameters and digestibility. Seventy-two dairy-beef bulls (465 kg; 16 months of age) were randomly allocated to one of four treatments supplemented with CaO2; in a coarse ration (1) CON (0% CaO2), (2) LO (1.35% CaO2), (3) HI (2.25% CaO2), and in a pellet (4) HP (2.25% CaO2) (n = 18). Animals received their respective treatments for a 77 d finishing period, during which DM intake (American Calan Inc., Northwood, NH), average daily gain (ADG), feed efficiency and enteric emissions (GreenFeed emissions monitoring system; C-Lock Inc., Rapid City, SD) were measured. The finishing diet was isonitrogenous and isoenergetic across the four treatment groups, composed of 60:40 grass silage:concentrate. Silage was offered each morning (0900 h), and concentrates were offered twice daily (0800 and 1500 h). Supplementation of CaO2 had no effect on final weight (P = 0.09), ADG (P = 0.22) or feed efficiency (P = 0.13). Regarding DM intake, the HI treatment group consumed in the order of 1 kg less than CON (P < 0.01), while HP did not affect DM intake compared to CON (P = 0.79). Across treatments, DM intake ranged from 8.43 to 9.57 kg/d, equating to 1.6–1.8% of BW. Daily CH4 values for the control were 240 g/d, while CaO2 supplemented diets ranged from 202 to 170 g/d, resulting in daily CH4 reductions of 16, 29 and 27% for LO, HI and HP, respectively, compared to CON (P < 0.0001). Additionally, hydrogen was reduced in CaO2 supplemented animals by 32–36% relative to CON (P < 0.0001), with a simultaneous reduction in volatile fatty acid production (P < 0.01) and an increase in propionate concentration (P < 0.0001). Across all universally accepted CH4 metrics (yield, intensity, production), the dietary inclusion of CaO2 whether at a low or high rate, or indeed, through a coarse ration or pelleted format reduced CH4 in the order of 16–32%. This study also concluded that CaO2 can successfully endure the pelleting process, therefore, improving ease of delivery if implemented at farm level.